Imam Suprayogo's Perspective on Contextualization in Education - Maidar Darwis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This research deals with Imam Suprayogo's Thought Contextualization in the World of Education. Contextualization is an effort to put things in context. The concept of science integration Imam Suprayogo has been Indonesian. The curriculum is an educational design that has a fairly central position in all educational activities and as a determinant of the implementation process and educational outcomes. The research method used in this study is descriptive analysis method or literature review. The finding shows that contextualization is an effort to put things in context. The concept of science integration Imam Suprayogo has been Indonesian. From several advantages of the integration concept initiated by him, many other universities tried to contextualize his thoughts in their respective campuses. And now, education programs have also begun to be discussed and implemented in several other Islamic Universities in Indonesia, such as UIN Raniry, Sunan Kalijaga UIN, Syarif Hidayatullah State Islamic University and several other Islamic Universities.